2008
DOI: 10.1111/j.1747-0285.2008.00653.x
|View full text |Cite
|
Sign up to set email alerts
|

A Theoretical Study on Interactions Between Mitoxantrone as an Anticancer Drug and DNA: Application in Drug Design

Abstract: This research is an effort to further understand the physicochemical interaction between the novel drug, mitoxantrone (MTX) and its biologic receptor, DNA. The ultimate goal is to design drugs that interact more with DNA. Understanding the physicochemical properties of the drug as well as the mechanism by which it interacts with DNA, it should ultimately allow the rational design of novel anti-cancer or anti-viral drugs. Molecular modelling on the complex formed between MTX and DNA presented that this complex … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
17
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(18 citation statements)
references
References 67 publications
(85 reference statements)
1
17
0
Order By: Relevance
“…These RNA-binding compounds may also show significant toxicity to normal cells. In fact, our experimental results demonstrated that the XIAP RNA-binding MX3 (subsequently identified as the chemotherapeutic drug mitoxantrone, which binds to numerous RNA and DNA molecules (Durr et al, 1983; Riahi et al, 2008; Zheng et al, 2009), had a strong inhibitory effect on normal human hematopoiesis and induced tissue damage in animal studies, although the toxicity could also come from other activities of this drug. Nevertheless, XIAP RNA-binding compounds may have limited clinical use.…”
Section: Discussionmentioning
confidence: 83%
“…These RNA-binding compounds may also show significant toxicity to normal cells. In fact, our experimental results demonstrated that the XIAP RNA-binding MX3 (subsequently identified as the chemotherapeutic drug mitoxantrone, which binds to numerous RNA and DNA molecules (Durr et al, 1983; Riahi et al, 2008; Zheng et al, 2009), had a strong inhibitory effect on normal human hematopoiesis and induced tissue damage in animal studies, although the toxicity could also come from other activities of this drug. Nevertheless, XIAP RNA-binding compounds may have limited clinical use.…”
Section: Discussionmentioning
confidence: 83%
“…According to what has been reported, the increment of RLS signals at 395 nm was attributed to the MIT-dsDNA complex, which was formed by the insertion of MIT molecule into the duplex of dsDNA. 31 Meanwhile, the hydrogen bond between the electronegative groups of MIT and dsDNA can also stabilize the MIT-dsDNA complex, 32 which also resulted in the remarkable enhancement of RLS signals. Based on the phenomenon above, we exercised the advantage of high sensitivity of RLS technique in the nucleotides research in vitro and brought it into different sequence systems.…”
Section: Resultsmentioning
confidence: 99%
“…It can insert into the duplex of DNA and form a complex, which can restrain the activity of polymerases of DNA and RNA, which is also the basis of its antitumor effect. 31 In this contribution, the selective non-covalent interaction between MIT and DNA has been investigated non-damagingly by the RLS strategy; especially the DNA sequence recognition of MIT was systematically studied and the selective mechanism was also discussed. In order to confirm the reliability of the RLS assay, atomic force microscope (AFM, Digital Instruments, Santa Barbara, CA, USA) and fluorescence method were also involved and the results confirmed that the RLS technique can be an effective and reliable method in the research of selectivity of anticancer drugs.…”
Section: Introductionmentioning
confidence: 99%
“…16 The strength of binding usually correlates with the target molecules tendency toward the ionophore, and several energy contributions may be responsible for the binding which is believed that amongst these energies, electrostatic interactions play a dominant role in the process at least in sequence preferences and the target molecules positioning. 17,18 There are no literature studies to date that have used DFTB methods to evaluate drug selective ligands by electronic properties. The lack of work in this area is probably due to the inherent difficulties associated with doing calculations on a Drug-Ligand complex.…”
mentioning
confidence: 99%